Embracing satellite libraries in academia. Issue 2 (3rd April 2017) - Turner, Laura Speirs
Abstract : Purpose: Satellite libraries in this study include print book collections located on the university campus but not within the walls of the main library nor under its administration. Addition of these collections to the university's integrated library system, evaluated and cataloged by the main library, represent significant and valuable collaboration between the university library and collection stakeholders. Design/methodology/approach: This case study discusses the development and best practices for a mutually beneficial relationship between the main library and on-campus satellite library partners at a medium-sized, private university. Findings: With systematic planning, effective partnerships between the main library and satellite library stakeholders can offer a university even more than discovery of research material. Originality/value: This paper includes examples of and practical advice for incorporating satellite libraries as additional materials promoted by the academic library system in an era of widespread resource sharing and collaboration.